PS 05-88 THE RELATIONSHIP OF RETINAL VESSEL DIAMETERS AND FRACTAL DIMENSIONS WITH BLOOD PRESSURE AND CARDIOVASCULAR RISK FACTORS. (September 2016) - Zhu, Pengli; Yuan, Yin; Huang, Feng; Lin, Fan
Abstract : Objective: This study aimed to investigate the correlation between quantitative retinal vascular parameters such as central retinal arteriolar equivalent (CRAE) and retinal vascular fractal dimension [D(f)], and cardiovascular risk factors in the Chinese Han population residing in the in islands of southeast China. Design and Method: In this cross-sectional study, fundus photographs were collected and semi-automated analysis software was used to analyze retinal vessel diameters and fractal dimensions. Cardiovascular risk factors such as relevant medical history, blood pressure (BP), lipids, and blood glucose data were collected. Results: Subjects had a mean age of 51.9612.0 years and included 812 (37.4%) males and 1, 357 (62.6%) females. Of the subjects, 726 (33.5%) were overweight, 226 (10.4%) were obese, 272 (12.5%) had diabetes, 738 (34.0%) had hypertension, and 1, 156 (53.3%) had metabolic syndrome. After controlling for the effects of potential confounders, multivariate analyses found that age ( β  = 0.06, P  = 0.008), sex ( β  = 1.33, P  = 0.015), mean arterial blood pressure ( β  = −0.12, P  < 0.001), high-sensitivity C-reactive protein ( β  = −0.22, P  = 0.008), and CRVE ( β  = 0.23, P  < 0.001) were significantly associated with CRAE. Age ( β  = −0.0012, P  < 0.001), BP classification (prehypertension: β  = −0.0075, P  = 0.014; hypertension: β  = −0.0131, P  = 0.002), and hypertension history ( β  = −0.0007, P  = 0.009) were significantly associated with D(f). Conclusions: D(f) exhibits a stronger association with BP than CRAE. Thus, D(f) may become a useful indicator of cardiovascular risk.